Hubungan Pengetahuan Ibu dengan Penggunaan Alat Kontrasepsi dalam Rahim (AKDR) di Puskesmas Putussibau Kabupaten Kapuas Hulu Tahun 2017 - Tri Maharani (Cendekia Medika: Jurnal Stikes Al-Ma`arif Baturaja, 2020)
Introduction: The rapid population growth rate has encouraged the Family Planning Program which was developed forty years ago (1968), and has only been enjoyed in recent years. This support emerged after the campaign was carried out through the PKBI that had been formed. At the world level, the family planning movement has succeeded in reducing the number of children per family from 3.9 to 2 children, especially in developed countries. In Indonesia, the use of IUDs is also very small, around 4.35% of other contraceptives. Data for the last year in the Puskesmas Putussibau, where the new family planning participants were 588 IUD users, only 1.5% (9 people). Objective: To determine the relationship between maternal knowledge and use of intrauterine contraceptives in the working area of ​​Puskesmas Putussibau, Kapuas Hulu Regency in 2017.Research Methodology: This study used a cross-sectional design with a survey approach. This research was conducted from 7 to 28 October 2017. The sample of the study was 68 WUS people at Puskesmas Putussibau, Kapuas Hulu District. Data analysis used was the Spearmen-Rank to determine the relationship between variables with the use of the IUD with a value of p = 0.042 (x2 = 2.10), which means that the relationship between the variables is significant. Conclusion: The results showed that there was a relationship between knowledge and IUD use.